2007
DOI: 10.1097/hjh.0b013e3282ef7a0a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the vasodilatory endothelial cannabinoid receptor in the human pulmonary artery

Abstract: Abnormal cannabidiol relaxes human pulmonary arteries in an endothelium-independent and endothelium-dependent manner. The latter component is probably mediated via the putative endothelial cannabinoid receptor, activation of which may release endothelium-derived hyperpolarizing factor, which in turn acts via calcium-activated potassium channels. Abnormal cannabidiol is behaviourally inactive; it may have a therapeutic implication in vascular diseases, especially in the treatment of pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 28 publications
7
70
2
Order By: Relevance
“…This receptor has been implicated in animal studies to be involved in mediating vasorelaxation to a range of cannabinoids in a variety of vascular beds, and is antagonised by an analogue of cannabidiol, O1918 [5], [26], [27], [28]. In agreement with these studies, we found that the effects of AEA in human mesenteric arteries were reduced by removal of the endothelium and in the presence of O-1918, further suggesting the existence of the proposed CB e receptor in humans [10], [23], [29]. The exact identity of this receptor is still unknown but a promising candidate is the orphan receptor GPR18.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This receptor has been implicated in animal studies to be involved in mediating vasorelaxation to a range of cannabinoids in a variety of vascular beds, and is antagonised by an analogue of cannabidiol, O1918 [5], [26], [27], [28]. In agreement with these studies, we found that the effects of AEA in human mesenteric arteries were reduced by removal of the endothelium and in the presence of O-1918, further suggesting the existence of the proposed CB e receptor in humans [10], [23], [29]. The exact identity of this receptor is still unknown but a promising candidate is the orphan receptor GPR18.…”
Section: Discussionsupporting
confidence: 86%
“…In human pulmonary arteries, AEA also caused maximal vasorelaxation [23]. However, in the present study, both the potency and efficacy of AEA were lower.…”
Section: Discussioncontrasting
confidence: 72%
“…However, in the same arteries, the vasorelaxant effect of 2-AG was not CB 1 mediated (Stanley and O'Sullivan 2014b). AEA and virodhamine-induced vasorelaxation of the human pulmonary artery is also not dependent on CB 1 (Kozlowska et al 2007;Kozlowska et al 2008;Baranowska-Kuczko et al 2014). …”
Section: Role For Cbmentioning
confidence: 79%
“…This is a finding common with a number of cannabinoid ligands in a range of vascular preparations [58,59] including human arteries [60]. To determine a potential role for calcium channels, some arteries were contracted using U46619 in calcium-free PSS, i.e.…”
Section: Discussionmentioning
confidence: 99%